Socio-Cultural Educational Environment of University as a Factor in the Development of Future Teacher’s Polysubjectness - E. N. Krolevetskaya; I. F. Isaev (Высшее образование в России)
The relevance of the research stems from the change in the role of a modern teacher, the transformation of the value foundations of the teaching profession, the complication of the teacher’s competencies. The process of professional training of a future teacher at university inevitably focuses on the development of his multidimensional subjective activity, which is characterized by the ability to choose options for achieving educational results, building life and professional prospects on their basis. In the context of modern scientific research, the concept of “teacher’s personality polysubjectness” is highlighted. An important factor in the development of the future teacher’s personality polysubjectness is the socio-cultural educational environment of university. The purpose of the study was to analyze the influence of the components of the socio-cultural educational environment of the university on the development of the future teacher’s polysubjectness. Methods of theoretical analysis, synthesis, generalization, self-assessment, and questionnaire were used in the work comprehensively. The research sample consisted of 328 1st-5th-year students of the Pedagogical Institute of the Belgorod National Research University majoring in “Pedagogical education”. Data collection was carried out in the 2020-2021 academic year. The reliability of the results was checked by methods of mathematical statistics (nonparametric Mann-Whitney test) using the IBM SPSS Statistics software package. Qualitative analysis of students’ reflexive judgments was also applied in understanding the phenomenon of polysubjectness and the role of university’s educational environment in its development. As a result of empirical research, it has been established that the multidimensional socio-cultural educational environment of the university is a determining developing factor influencing on changes in the structure of the future teacher’s personality polysubjectness. The university’s educational environment has the greatest influence on such components of polysubjectness as the ability to interact, emotional intelligence, situational leadership.